Mitochondrial haplogroup M contributes to asthma risk in the Kuwaiti population - Dashti, Mohammed; Bahbahani, Hussain; Alsaleh, Hussain; Thanaraj, Thangavel Alphonse; Al-Mulla, Fahd (Frontiers in Allergy, 2025)
BackgroundAsthma is a multifactorial chronic inflammatory disease characterized by intermittent airflow obstruction, which may result in irreversible pathological remodelling of the airways. In Kuwait, the prevalence of asthma among young adults is approximately 11%, with a strong maternal influence on asthma risk. While nuclear genetic studies have identified several asthma-associated loci, the role of maternally inherited mitochondrial DNA (mtDNA) in asthma susceptibility remains poorly understood, particularly in Middle Eastern populations.MethodsIn this exploratory study, we analysed mtDNA from 287 Kuwaiti individuals, including 48 asthmatics and 239 controls, extracted from whole-exome sequencing data (average coverage 27×), with variant calling via GATK and haplogroup assignment using HaploGrep2. Logistic regression was used to assess associations between mtDNA variants/haplogroups and asthma, adjusting for age, sex, and BMI.ResultsMitochondrial haplogroup M was identified as a significant risk factor for asthma (OR = 3.37; 95% CI = 1.09–10.42; P = 0.035). Additionally, we identified fourteen mtDNA variants associated with asthma risk through complementary case-control and exclusivity analyses. These variants are located within genes encoding subunits of mitochondrial Complex I (MT-ND1, MT-ND3, MT-ND5), Complex III (MT-CYB), Complex IV (MT-CO1, MT-CO2), and the mitochondrial control region. Most are linked to dysfunction and reactive oxygen species (ROS) production, key processes implicated in asthma pathogenesis.ConclusionsOur findings suggest that mitochondrial haplogroup M and specific mtDNA variants contribute to asthma susceptibility in the Kuwaiti population. These insights provide a foundation for future research on mitochondrial genetic influences in asthma and highlight the need for larger studies to validate these associations and explore potential therapeutic implications.